The Comparative Analysis of Onegin Stanzas by Puškin and Baratynskij - Grinbaum, Oleg (Respectus Philologicus, 2002)
This paper presents the main results of rhythmic-harmonic and metric-syntaxical parameters in the two poems: Eugenie Onegin by Pushkin and Beil by Baratynskii. The poems have been analyzed by the author's own method of rhythmic-harmonic exactness, based on the golden section principle and Fibonacci dynamic numerical series. The results of the analysis make it possible to confirm mathematically Pushkin's appreciation of the poem Beil as a poetic masterpiece and to demonstrate some peculiarities of Baratynskij's style, which does not prevent him from achieving very high level of classical Russian poetry, represented by Pushkin in his novel Eugenie Onegin.